OPTIMASI PROSES PENGOMPOSAN SAMPAH ORGANIK DENGAN SISTEM AERASI DALAM KOMPOSTER - MUZAKI, A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Problems of urban waste currently have received considerable attention because it has caused serious environmental pollution. Advances in technology have brought changes to the welfare of human beings, but the technology will also have a negative impact on the environment in the form of waste. Waste management and utilization is needed to address the problem of waste. One alternative to optimize the process of composting organic waste so that the waste management and utilization of more effective. The purpose of this study to determine the effect of the composition of the additives EM4 and Yeast Compost under optimum conditions with aeration control for composting time, and determine the effectiveness of the composition of the EM4 and Yeast Compost additives with aeration control on the quality of the compost. The method used is composting with the addition of additives EM4 and yeast Compost with 5 variations of 300 gr : 0 ml for R.1, 225 g : 75 ml for R.2, 150 g : 150 ml for R3, 75 g : 225 ml to R4, and 0 g : 300 ml for R5. Assessment conducted during the composting process, including: daily temperature measurements, pH, moisture, and the quality of the compost and use a special composter tub with a particular treatment. Chemical quality includes N, C, C / N ratio, moisture content, P and K. Composting cooked if the temperature, pH and humidity has stabilized. The research design was using completely randomized design (CRD). The analyzing was using ANOVA. The results of research indicated that the composition of additives EM4 and Yeast Compost the optimum conditions with aeration control can accelerate the composting time on substance additive 75 ml EM4 : 225 g Yeast Compost lasted 24 days and produce compost that meets ISO standards 19_7030_2004.